Fire and home range expansion: A behavioral response to burning among savanna dwelling vervet monkeys (Chlorocebusaethiops). Issue 4 (3rd June 2014) - Herzog, Nicole M.; Parker, Christopher H.; Keefe, Earl R.; Coxworth, James; Barrett, Alan; Hawkes, Kristen
ABSTRACT The behavioral adaptations of primates to fire‐modified landscapes are of considerable interest to anthropologists because fire is fundamental to life in the African savanna—the setting in which genus Homo evolved. Here we report the behavioral responses of a savanna‐dwelling primate, vervet monkeys (Chlorocebus aethiops), to fire‐induced ecological change. Using behavioral and spatial data to characterize ranging patterns prior to and postburn and between burn and nonburn years, we show that these primates inhabiting small, spatially bound, riverine habitats take advantage of newly burned savanna landscapes. When subjects encountered controlled fires, they did not flee but instead avoided the path of the fire seemingly unbothered by its approach. After fire, the primates' home range expanded into newly burned but previously unused areas. These results contribute to understanding the response of non‐human primates to fire‐modified landscapes and can shed light on the nature and scope of opportunities and constraints posed by the emergence of fire‐affected landscapes in the past. Results also expose deficiencies in our knowledge of fire‐related behavioral responses in the primate lineage and highlight the need for further investigation of these responses as they relate to foraging opportunities, migration, resource use, and especially fire‐centric adaptations in our own genus. Am J Phys Anthropol 154:554–560, 2014. © 2014 Wiley Periodicals, Inc.